A critical evaluation of large scale development projects and programmes in South Africa - Thwala, Wellington D.; McCutcheon, R.T. (University of the Witwatersrand. History Workshop., 1999)
South Arica needs employment-intensive infrastructure programmes in order to create jobs. Local needs and communities ideas must be taken into account. Quality and cost effectiveness should not be compromised. The supervisors should be technically and organisationally competent. Sustainable finance and a reliable political will to see the projects though are essential.
Paper presented at the Wits History Workshop: Forging the links between historical research and the policy process, 18-19 September 1999.
Keywords: Economic development. South Africa; Job creation. South Africa